A Systematic Study of Compositionally Dependent Dielectric Tensors of SnSxSe1-x Alloys by Spectroscopic Ellipsometry - Xuan Au Nguyen; Thi Minh Hai Nguyen; Tae Jung Kim; Long Van Le; Tung Hoang Nguyen; Bogyu Kim; Kyujin Kim; Wonjun Lee; Sunglae Cho; Young Dong Kim (Crystals, 2021)
We report the dielectric tensors on the cleavage plane of biaxial SnSxSe1-x alloys in the spectral energy region from 0.74 to 6.42 eV obtained by spectroscopic ellipsometry. Single-crystal SnSxSe1-x alloys were grown by the temperature-gradient method. Strongly anisotropic optical responses are observed along the different principal axes. An approximate solution yields the anisotropic dielectric functions along the zigzag (a-axis) and armchair (b-axis) directions. The critical point (CP) energies of SnSxSe1-x alloys are obtained by analyzing numerically calculated second derivatives, and their physical origins are identified by energy band structure. Blue shifts of the CPs are observed with increasing S composition. The fundamental bandgap for Se = 0.8 and 1 in the armchair axis arises from band-to-band transitions at the M0 minimum point instead of the M1 saddle point as in SnS. These optical data will be useful for designing optoelectronic devices based on SnSxSe1-x alloys.